Preditores de sarcopenia em pacientes com doença renal crônica submetidos à hemodiálise - Ripardo, Khataryna Khauane Brandão (2024)
Introduction: Chronic kidney disease (CKD) is a public health problem that has been increasing in number of people over time. Patient with CKD who underwent dialysis throughout his life. Among the complications, attention is drawn to the loss of lean mass. This loss of lean mass favors the appearance of other complications, sarcopenia, which is characterized by the loss of lean mass and a decrease in muscle strength. Sarcopenia has a major impact on the lives of these patients. Therefore, the objective of this study is to study the risk factors associated with sarcopenia in patients with chronic kidney disease on dialysis. Methods: This is a cross-sectional research, with patients with chronic kidney disease on dialysis, carried out in 2023 at the Hemodialysis Center of Santa Casa de Misericórdia de Sobral. Patients aged 18 years or over, from both sexes. And patients with cognitive disability, reported rheumatological problems and total hearing impairment were excluded. All patients were on conventional hemodialysis. Data collection took place between May and June 2023, the study sampling was by convenience. 152 patients participated in the research. The following were assessed: sociodemographic profile, comorbidities using the Khan index, a dynamometer was used to assess sarcopenia and a 24-hour dietary record was used to assess food consumption. For statistical analysis, univariate and multivariate analysis was used considering the 95% confidence interval and statistically significant p =< 0.05. Results: With the assessment of sarcopenia, it was detected that 52% were sarcopenic and 48% were not sarcopenic. Regarding food consumption, food consumption in kcal/kg/day and protein grams/kg/day was lower than the recommendations recommended today. Furthermore, patients with a medium or high-risk Khan index were 3 times more likely to have sarcopenia and older patients were also more likely. Discussion: This study investigated the risk factors for sarcopenia in patients with chronic kidney disease on dialysis and their potential related factors in a sample of patients in the interior of Ceará. Conclusion: Patients with chronic kidney disease on dialysis are more susceptible to developing sarcopenia as they age and have more comorbidities.